CRISPR-Cas Defense System and Potential Prophages in Cyanobacteria Associated with the Coral Black Band Disease - Buerger, Patrick; Wood-Charlson, Elisha M.; Weynberg, Karen D.; Willis, Bette L.; van Oppen, Madeleine J. H. (Frontiers in Microbiology, 2016)
Understanding how pathogens maintain their virulence is critical to developing tools to mitigate disease in animal populations. We sequenced and assembled the first draft genome of Roseofilum reptotaenium AO1, the dominant cyanobacterium underlying pathogenicity of the virulent coral black band disease (BBD), and analyzed parts of the BBD-associated Geitlerinema sp. BBD_1991 genome in silico. Both cyanobacteria are equipped with an adaptive, heritable CRISPR-Cas defense system type I-D and have potential virulence genes located within several prophage regions. The defense system helps to prevent infection by viruses and mobile genetic elements via identification of short fingerprints of the intruding DNA, which are stored as templates in the bacterial genome, in so-called "clustered regularly interspaced short palindromic repeats" (CRISPRs). Analysis of CRISPR target sequences (protospacers) revealed an unusually high number of self-targeting spacers in R. reptotaenium AO1 and extraordinary long CRIPSR arrays of up to 260 spacers in Geitlerinema sp. BBD_1991. The self-targeting spacers are unlikely to be a form of autoimmunity; instead these target an incomplete lysogenic bacteriophage. Lysogenic virus induction experiments with mitomycin C and UV light did not reveal an actively replicating virus population in R. reptotaenium AO1 cultures, suggesting that phage functionality is compromised or excision could be blocked by the CRISPR-Cas system. Potential prophages were identified in three regions of R. reptotaenium AO1 and five regions of Geitlerinema sp. BBD_1991, containing putative BBD relevant virulence genes, such as an NAD-dependent epimerase/dehydratase (a homologue in terms of functionality to the third and fourth most expressed gene in BBD), lysozyme/metalloendopeptidases and other lipopolysaccharide modification genes. To date, viruses have not been considered to be a component of the BBD consortium or a contributor to the virulence of R. reptotaenium AO1 and Geitlerinema sp. BBD_1991. We suggest that the presence of virulence genes in potential prophage regions, and the CRISPR-Cas defense systems are evidence of an arms race between the respective cyanobacteria and their bacteriophage predators. The presence of such a defense system likely reduces the number of successful bacteriophage infections and mortality in the cyanobacteria, facilitating the progress of BBD.